METODE PROYEK TERHADAP KETERAMPILAN MEMILAH SAMPAH SISWA TUNANETRA DI SEKOLAH MENENGAH PERTAMA LUAR BIASA - DEWWA RISONA ANDITTA, LOUKIS (Jurnal Pendidikan Khusus, 2017)
Abstract Learning skill was one of the learning which was really required by the blind. Learning skill could also be used as facility to enhance cognitive ability in understanding lesson material. The skill of science process, which could be applied to the blind students, was selecting organic and inorganic garbage skill. The developing of selecting garbage was aimed in order that the children could differentiate the organic and inorganic garbage using project method. A project method was learning which build the students’ motivation to be more active in solving problem dealing with processing garbage. This research purpose was to apply the project method toward selecting garbage skill to the blind students. This research used quantitative approach and pre-experiment kind. The research arrangement was “one group, pretest – posttest design” with the research subject i.e. the blind students of class VII numbering 7 students. The research location was in SMPLB-A YPAB Surabaya. The data collection method used test and the technique of data analysis used statistic non parametric of sign test. Based on the data analysis it indicated that ZH = 2,05 > Z table = 1,96 to 5% significant level (two sides test). So, it could be concluded that there was significant influence toward selecting garbage skill to the blind students using project method in SMPB-A YPAB Surabaya.     Keywords:  project method, selecting garbage.